SUBSTANTIATION AND GUARANTEEING OF TECHNOLOGICAL PARAMETERS OF TRIBOELECTRICAL METHOD OF MONITORING OF CABLES WITH POLYMER INSULATION - A.V. Bezprozvannych (National Technical University "Kharkiv Polytechnic Institute", 2014)
The results of measurements of the contact potential difference of not shielded and shielded samples of cables with twisted pair without shielded chamber, inside a shielded non-grounded and grounded camera are presented. Inspections carrying out in a grounded chamber are more effective in the case of shielded cables. It is shown that utilization of an electrostatic voltmeter with higher sensitivity in comparison with digital voltmeter leads to registration as individual own internal noises of the cable as external ones. The coefficients of correlation between the results of measurements of the contact potential difference of the power cable by electrostatic voltmeter and by digital multimeter are determined.